Youth Employment Programs : An Evaluation of World Bank and International Finance Corporation Support - Independent Evaluation Group (Washington, DC: World Bank, 2013)
Youth employment issues are a major concern for many countries because they have negative effects on the welfare of young people, and may also adversely affect economic performance and social stability. This is the first Independent Evaluation Group (IEG) evaluation of the World Bank Group's support to countries trying to address youth employment issues. The World Bank lending portfolio for youth employment is relatively small, although components of programs appear in 57 countries. Most projects include interventions in skills development and school-to-work transition. Half of the projects include interventions to foster job creation and work opportunities for youth. International Finance Corporation (IFC) has a broad approach to job creation. Between FY01 and FY11 youth employment has not been specifically targeted, except in the Middle East and North Africa region and in a small number of other interventions. IFC invested $500 million to 50 investment operations and 18 advisory services to education. Although youth employment is addressed in the education, social protection, and labor strategies, it is not recognized as an issue in most country strategies even where youth unemployment is serious. Youth employment is a multisectoral issue, but few youth employment projects are implemented by multisectoral teams. The evaluation makes two recommendations: (i) apply an evidence-based approach to youth employment operations, and (ii) at the country level, take a strategic approach to youth employment by addressing the issue comprehensively, working across World Bank Group teams, with governments and other donors. There is a critical need to strengthen evidence-based feedback loops to the strategic planning process. Addressing youth employment issues is a major concern for many countries. It negatively affects the welfare of young people and potentially the rest of the economy as well. Unemployed youth do not get a chance to build professional skills. As a result, they are more at risk for higher adult unemployment, career downgrades and lower wages later in life, and a loss in lifetime earnings. The reasons for higher youth-to-adult unemployment rates include labor demand and supply factors, as well as constraints in the labor and credit markets. Their relative importance in a dynamic growth context varies across countries. Recognizing these differences is important for governments in designing youth employment programs tailored to the most affected youth groups, and to incorporating in program design specific interventions to address the underlying causes of youth unemployment and underemployment. This evaluation was done to better understand the contributions of the World Bank and IFC to these efforts, their effectiveness, and what can be learned from the experience to support decision makers in finding new solutions.